Uji Validitas Lembar Kerja Siswa (LKS) Biologi SMA Berbasis Model Pembelajaran Double Loop Problem Solving (DLPS) pada Materi Ekosistem untuk Meningkatkan Pemahaman Konsep - Linda Ayu Setyaningsih; Tabitha Sri Hartati Wulandari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
This study aims to determine the validity of Student Worksheet (LKS) Biology Based Learning Model Double LOOP Problem Solving (DLPS) on the material Ecosystem for high school. This research is a development research, using Borg & Gall model. This model consists of 10 development stages: Research and data collection, Planning, Product draft development, Initial field trials, Revising test results, Field trials, Completion of field test results, Completion of final product, Dissemination and implementation. Implementation of development steps tailored to the needs of researchers. Given the limited time and funds owned by researchers, these steps are simplified into four development steps: Data collection phase, Planning phase, Product development stage, Stage validity. This research was conducted in July 2018. This research was conducted in MA Syiar Islam. The data collected in this research is the data of LKS validity test by matri and media experts. This research data is analyzed by using descriptive statistic in the form of percentage. The results of the validity of the material experts 82.5% and the media experts 82.58% withcriteria is very valid. It is concluded that the results of LKS product validation test developed can be used to improve concept understanding.